Strength Characteristics of OSB in Bending – Difference between Upper and Lower Panel Faces - Martin Böhm (University of Zagreb, Faculty of Forestry and Wood Technology, 2011)
This article is focused on evaluating the differences between the upper and lower faces of OSB/3 – Superfinish in the course of bending stress. OSB is a material manufactured from wood chips of a large surface area, irregular shape and unequal length, which are partly randomly distributed and at the same time not perfectly oriented. Differences regarding the content of OSB surface layers cause unequal properties, which can be demonstrated, especially under bending load. The measurements made show that OSB positioned with upper face downwards in the course of the bending test are capable of withstanding a higher load, and reaching an evidentially lower deflection, compared to those with lower face downwards.